Antimicrobial Resistance Patterns of Escherichia Coli Isolated from Beef, Mutton and Chevon in the Greater Accra Region of Ghana - Dsani, E.N.D. (University of Ghana, 2019)
Background Antimicrobial resistance (AMR) poses a challenge to the health of the populace. Food producing animals (FPA) are major reservoirs for food-borne pathogens, which may be resistant to critically needed antimicrobials in human and veterinary medicine. Contamination of raw meat with Escherichia coli (E. coli) strains may occur during slaughter and sale. The presence of E. coli that have the ability to produce extended spectrum beta lactamase (ESBL), affect treatment outcomes for life-threatening infections in humans. We determined the presence of E. coli in raw meat, characterized their antimicrobial susceptibility patterns and detected the resistant genes associated with the extended spectrum beta-lactamase enzyme. Methods We collected surface swabs from cattle (81), sheep (16) and goats (108) after slaughter from three slaughterhouses in the Greater Accra Region. With the aid of a template and sterile cotton swab, we sampled an area of 300 cm2 from the flank, brisket and upper thigh in cattle, and an area of 75 cm2 from the flank, brisket and mid-loin for sheep and goats. We performed total viable counts, coliform counts, and cultured samples on MacConkey agar following enrichment in Brain Heart Infusion (BHI). Based on their colonial morphology, E. coli isolates were identified. Confirmation was carried out using the Matrix- assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF) system.We tested the susceptibility of isolates to 11 antibiotics using the Kirby Bauer disk diffusion method. We performed the combination disk test for screening of ESBL’s in all E. coli isolates that had resistance to cephalosporins. We subsequently screened these isolates for ESBL resistant genes (CTX, SHV and TEM) by Polymerase Chain Reaction (PCR). We observed slaughter practices. Descriptive statistics was used to characterize antimicrobial susceptibility patterns. Results The mean total viable count was 5.03 (±1.06) log CFU/cm2) for the 205 samples collected. This exceeds the limit of 5.0 log CFU/cm2, for total viable microbial counts for cattle, sheep and goat carcasses. For Enterobacteriaceae, high counts were reported at Tema slaughterhouse and Tulaku slaughter slab (3.12±0.2 and 3.87±0.7). Overall, prevalence of E. coli was 48% (98/205) in all meat types sampled. Antimicrobial susceptibility testing showed that isolates exhibited resistance to ampicillin (57%; 56/98), tetracycline (45%; 44/98), sulfamethoxazole-trimethoprim (21%; 21/98), cefuroxime (17%; 17/98), ciprofloxacin (8% ;8/98) and cefotaxime (2%; 2/98). Meropenem showed the highest rate susceptibility(100%). Multi-drug resistance was identified in 22% (22/98) of isolates. Four (4) isolates were found to have the TEM gene. Water supplies, sanitary facilities, work area and equipment at all sites were found to be sub-standard per the guidelines set by the Ghana Food and Drugs Authority (FDA). Conclusion Contamination with E. coli was found to be high in raw meat. The presence of ESBL-producers among E. coli found in meat, has implications for the management of local and systemic infections in humans. Sub-optimal slaughter practices might have facilitated contamination. There is an urgent need to monitor the hygiene process at slaughter sites and to educate slaughterhouse workers on hygienic practices.
MPhil. Applied Epidemiology and Disease Control
Keywords: Foodborne Pathogens; Food Safety; Escherichia Coli; Raw Meat; Greater Accra